A qualitative exploration of the mental health challenges and therapeutic needs of Canadian correctional workers - Moghimi, Elnaz; Knyahnytska, Yuliya; Zhu, Yiran; Kumar, Anchan; Knyahnytski, Alexander; Patel, Charmy; Omrani, Mohsen; Gerritsen, Cory; Martin, Michael; Simpson, Alexander Ian Frederic; Alavi, Nazanin (Frontiers in Psychiatry, 2022)
Purpose: Correctional work is described as a high-stress environment associated with increased prevalence of mental health disorders in employees. Identifying appropriate healthcare services necessitates investigating the mental health challenges and needs of correctional workers (CWs). Methods: Individual interviews (n = 9; 5 M and 4 W) and a mixed gender focus group (n = 6; 3 M and 3 W) were conducted to gather a general sense of the mental health landscape. Data were analyzed to develop a targeted and comprehensive question guide for gender-specific focus groups (n = 14 unique participants; 6 M and 8 W). Results: Eight themes emerged from the gender-specific focus groups. Themes focusing on work culture described the negative repercussions of job stress and the inability to discuss challenges openly due to confidentiality concerns and feelings of seclusion associated with the CW profession. Men were more likely to be subjected to physical violence and women to emotional and sexual harassment from staff and inmates. Themes related to mental health care described the benefits and limitations of the current services and digital mental healthcare. Stigma and accessibility were notable treatment barriers. Lastly, sector-specific therapy was seen as an important component in enhancing engagement and therapist interaction. Conclusions: The study demonstrates the interconnection between work culture and CW mental health that needs to be acknowledged when addressing mental health care.